The role of working memory capacity and speed of lexical access in speech recognition in noise - Larsby, Birgitta; Hällgren, Mathias; Lyxell, Björn (Proceedings of the International Symposium on Auditory and Audiological Research, 2011)
Cognitive skills are important for speech processing and comprehension. The objective of the present investigation was to address the role of working memory capacity and speed of lexical access in speech processing in noise. This was done by measuring speech recognition thresholds (SRTs) in background noise with the Hagerman test and the Swedish HINT. Cognitive capacities were measured by a lexical-decision making test and a reading- span test. Forty hearing impaired individuals, aged 44-86 years, participated in the study. The relations between SRTs and cognitive scores were studied using correlation analyses and analysis of variance for high and low cognitive performance groups. The individuals showed significant correlations between SRTs and cognitive scores which remained also after correcting for PTA4. A higher demand on cognitive processing was found for the criteria of 80% compared to 50 % speech recognition.